Leadership in Action : Issues and Observations - Taking Charge - Your First 100 Days on the Job - Campbell, David (Center for Creative Leadership, 2003)
Here are twenty-five suggestions on what to do during your first one hundred days in your new position. The suggestions are based on personal observations, interviews, seminar discussions, psychological test data, and anecdotes from leaders who have been in this situation.